2016
DOI: 10.3390/ijerph13080780
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Public Attention to the Outbreak of Ebola in West Africa: Evidence from the Online Big Data Platform

Abstract: Objective: The outbreak of the Ebola epidemic in West Africa in 2014 exerted enormous global public reaction via the Internet and social media. This study aimed to investigate and evaluate the public reaction to Ebola in China and identify the primitive correlation between possible influence factors caused by the outbreak of Ebola in West Africa and Chinese public attention via Internet surveillance. Methods: Baidu Index (BDI) and Sina Micro Index (SMI) were collected from their official websites, and the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…The use of social media pertaining to infectious disease and outbreak situations was another common thread within this theme, and was addressed by seventeen (43%) of the papers. Seven of these articles focused on the use of social media within the recent Ebola outbreak of 2013-2014 [3,9,38,42,46,57] eight others highlighted social media use in recent influenza/MERS, and dengue fever and bubonic plague outbreaks [30,32,40,41]; Yoo et al, 2016;[26,28,29]. Two papers analyzed social media response following news coverage of the Zika Virus [51,57].…”
Section: Theme 2: Infectious Disease and Outbreak Situationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of social media pertaining to infectious disease and outbreak situations was another common thread within this theme, and was addressed by seventeen (43%) of the papers. Seven of these articles focused on the use of social media within the recent Ebola outbreak of 2013-2014 [3,9,38,42,46,57] eight others highlighted social media use in recent influenza/MERS, and dengue fever and bubonic plague outbreaks [30,32,40,41]; Yoo et al, 2016;[26,28,29]. Two papers analyzed social media response following news coverage of the Zika Virus [51,57].…”
Section: Theme 2: Infectious Disease and Outbreak Situationsmentioning
confidence: 99%
“…There is also a need for innovative strategies such as the use of social media to address issues of SRH, empowerment, selfesteem, desires and professional aspirations of HIV-positive adolescents within HIV and AIDS programs. 22 Liu et al 2016 In order to understand and evaluate public reaction in China to the Ebola outbreak in West Africa in 2014 through Internet surveillance, Baidu Index (BDI) and Sina Micro Index (SMI) data were collected from their official websites. Hotspot areas were identified and qualitative analysis indicated public attention increased with negative news until the appearance of a positive news statement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although application of big data in Africa is still in its infancy, recent reports have shown that success has been achieved through the use of digital surveillance to track epidemics (Nsoesie et al, 2015;Chang et al, 2009;Liu et al, (2016)). Even though there are ethical issues to contend with in the use of big data in Africa, an outbreak of an epidemic, sometimes many epidemics become a national crisis as well as a global crisis.…”
Section: Big Data Application Through the Use Of Digital Surveillancementioning
confidence: 99%
“…A YouTube video uploaded by the New York Times entitled "Ebola Virus Outbreak 2014 which has been viewed over 1.5 million times as of April 26, 2015 showed a young man dying from Ebola outside a healthcare facility in West Africa. At the end of the video, the father of the young man is shown walking away with cash in his hand, which has led commenters to believe the video is a dramatization or propaganda [16,20,25]. Therefore, social media misinformation, fear mongering and information abuse does not only lead to lack of trust in government and health officials, but may desensitize individuals to the severity of the virus.…”
Section: Introductionmentioning
confidence: 99%